P2X4 receptor re‐sensitization depends on a protonation/deprotonation cycle mediated by receptor internalization and recycling. (17th September 2018) - Fois, Giorgio; Föhr, Karl J.; Kling, Carolin; Fauler, Michael; Wittekindt, Oliver H.; Dietl, Paul; Frick, Manfred
Abstract : Key points: Re‐sensitization of P2X4 receptors depends on a protonation/de‐protonation cycle Protonation and de‐protonation of the receptors is achieved by internalization and recycling of P2X4 receptors via acidic compartments Protonation and de‐protonation occurs at critical histidine residues within the extracellular loop of P2X4 receptors Re‐sensitization is blocked in the presence of the receptor agonist ATP Abstract: P2X4 receptors are members of the P2X receptor family of cation‐permeable, ligand‐gated ion channels that open in response to the binding of extracellular ATP. P2X4 receptors are implicated in a variety of biological processes, including cardiac function, cell death, pain sensation and immune responses. These physiological functions depend on receptor activation on the cell surface. Receptor activation is followed by receptor desensitization and deactivation upon removal of ATP. Subsequent re‐sensitization is required to return the receptor into its resting state. Desensitization and re‐sensitization are therefore crucial determinants of P2X receptor signal transduction and responsiveness to ATP. However, the molecular mechanisms controlling desensitization and re‐sensitization are not fully understood. In the present study, we provide evidence that internalization and recycling via acidic compartments is essential for P2X4 receptor re‐sensitization. Re‐sensitization depends on a protonation/de‐protonation cycle of critical histidine residues within the extracellular loop of P2X4 receptors that is mediated by receptor internalization and recycling. Interestingly, re‐sensitization under acidic conditions is completely revoked by receptor agonist ATP. Our data support the physiological importance of the unique subcellular distribution of P2X4 receptors that is predominantly found within acidic compartments. Based on these findings, we suggest that recycling of P2X4 receptors regulates the cellular responsiveness in the sustained presence of ATP. Key points: Re‐sensitization of P2X4 receptors depends on a protonation/de‐protonation cycle Protonation and de‐protonation of the receptors is achieved by internalization and recycling of P2X4 receptors via acidic compartments Protonation and de‐protonation occurs at critical histidine residues within the extracellular loop of P2X4 receptors Re‐sensitization is blocked in the presence of the receptor agonist ATP